PERAN MEDIASI EXPORT MARKET ORIENTATION PADA PENGARUH INTERNATIONAL ENTREPRENEURIAL ORIENTATION TERHADAP EXPORT PERFORMANCE - Agus Satria Pramudana, Komang; Santika, I Wayan (Buletin Studi Ekonomi, 2023)
This research is motivated by a decline in sales to SMEs in Bali due to the COVID-19 pandemic that has hit the whole world. The government is promoting exports to anticipate a weakening local market because of the COVID-19 pandemic. The purpose of this study was to analyze the mediating role of export market orientation on the effect of international entrepreneurial orientation on export performance in export SMEs in Bali. The data in this study will be obtained by distributing questionnaires to export SMEs in Bali. Testing the validity of the data used validity testing and reliability testing. Data analysis techniques using descriptive statistical analysis and inferential statistical analysis (SEM-PLS). The results of the study show that international entrepreneurial orientation has a positive and significant effect on export performance. Export market orientation has a positive and significant effect on export performance. Export market orientation positively and significantly mediates the effect of international entrepreneurial orientation on export performance. The mediating role of export market orientation is partial mediation in the influence of international entrepreneurial orientation on export performance in export SMEs in Bali.